THE INFLUENCE OF LITERACY, TOLERANCE, AND EXPERIENCE ON INVESTMENT DECISIONS OF GENERATION Z IN SURABAYA - Kevin Halim; Leonardo Christian Susanto; Sautma Ronni Basana (Petra Christian University, 2026)
The increasing participation of Generation Z in the Indonesian capital market needs to be balanced with the ability to make rational investment decisions in accordance with their risk profile. This study aims to analyze the influence of financial literacy, risk tolerance, and investment experience on the investment decisions of Generation Z investors in Surabaya. The study used a quantitative explanatory approach with a purposive sampling technique. The study respondents consisted of 225 Generation Z investors aged 18–29 years, domiciled in Surabaya, owning shares in the capital market, and having a customer fund account. Data were collected through an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that financial literacy had no significant effect on investment decisions. Risk tolerance had a positive and significant effect on investment decisions. Investment experience also had a positive and significant effect. These three variables explained 33.0% of the variation in investment decisions. These findings indicate that Generation Z investment decisions are more determined by readiness to face risks and direct experience in the capital market than by mastery of basic financial concepts. Therefore, investment education programs need to focus on fundamental analysis, technical analysis, investment simulations, and portfolio risk management.